2020
DOI: 10.1097/nan.0000000000000377
|View full text |Cite
|
Sign up to set email alerts
|

Reducing Risks and Improving Vascular Access Outcomes

Abstract: Short peripheral catheter (SPC) insertion is a common invasive procedure performed in hospitalized patients. Variations in this fundamental nursing skill exist among nurses, with significant impacts on budgets, patient satisfaction, and worker safety―key concerns for nurse leaders. A performance improvement project focused on vascular access management was undertaken, with the goal to improve SPC practice and associated outcomes. Assessment of current SPC policies, practices, products, and outcomes identified … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 28 publications
0
11
0
Order By: Relevance
“…This finding is lower than most studies conducted in Portugal, with complications rates varying between 50% and 62.1% [33,34,39,53], although none of the studies was conducted in an oncology setting. Several risk factors can be attributed to the existing complication rate in this specific cohort, namely patient age, gender, immune system suppression or high body mass index [5,54,55]. However, nurses' practices potentially explain some of the found complications, since poor patient involvement, adherence to aseptic technique, catheter stabilization and dressing integrity, and catheter flushing can lead to high incidence rates of infiltration and phlebitis.…”
Section: Discussionmentioning
confidence: 99%
“…This finding is lower than most studies conducted in Portugal, with complications rates varying between 50% and 62.1% [33,34,39,53], although none of the studies was conducted in an oncology setting. Several risk factors can be attributed to the existing complication rate in this specific cohort, namely patient age, gender, immune system suppression or high body mass index [5,54,55]. However, nurses' practices potentially explain some of the found complications, since poor patient involvement, adherence to aseptic technique, catheter stabilization and dressing integrity, and catheter flushing can lead to high incidence rates of infiltration and phlebitis.…”
Section: Discussionmentioning
confidence: 99%
“…Midline catheter failures can lead to increases in vein trauma, staff time, length of stay, and overall costs of health care 18. Delays in treatment from interruption of the prescribed therapy can decrease infusate effectiveness, lower patient satisfaction, and lead to poor outcomes 17–20. This study investigated the role of catheter material as a factor influencing the probability of completing the prescribed therapy.…”
Section: Discussionmentioning
confidence: 99%
“…A mean of 1.17 attempts per catheter were needed to achieve insertion, somewhat lower than the figures reported in other studies (Deutsch et al, 2014; Lisova et al, 2018; Scoppettuolo et al, 2016; Spiegel et al, 2020). This result is promising since, in clinical practice, it is extremely important to achieve successful catheter placement with as few attempts as possible and thereby minimize patient suffering (Morrell, 2020). Specifically, Bortolussi et al (2015) observed low levels of pain and distress during catheterisation with PICCs and midlines, implying that the insertion of these devices with a high first attempt success rate significantly improves the overall quality of life of these patients.…”
Section: Discussionmentioning
confidence: 99%